The No‐men of England: The Geordie Revolt that Defeated the Scotland and Wales Bill in 1977. Issue 4 (9th June 2016) - McLean, Iain
Abstract: The Scotland and Wales Acts 1978 failed on multiple criteria. Although devolution of powers to Scotland and Wales was a principal policy of the Labour governments in office from 1974 to 1979, it was defeated in a guillotine vote in 1977. That defeat was orchestrated by the leaders of Tyne & Wear County Council, angry that a government of their own party was apparently neglecting their region in favour of Scotland. The project was rescued in two separate bills, but a further rebel amendment inserted a minimum assent condition in the required referendums. The people of Wales rejected the devolution they were offered. The people of Scotland accepted it, but by a margin that failed to cross the threshold. The resulting vote of confidence brought down the Labour government in March 1979. The role of Tyne & Wear County Council in killing the first bill has never been fully acknowledged. The lessons of the story for current devolution policy are explored. If the UK remains a single country, any policy for tax transfers must be fair to the English as well as to the people of the other three territories.